Infectious morbidity of speculum versus digital examinations in preterm prelabor rupture of membranes: a systematic review and meta-analysis. (12th December 2022) - Ayyar, Archana; Moufarrij, Sara; Turrentine, Mark
Abstract: Objective: To estimate the effect of speculum examination only versus digital cervical examination on maternal infectious morbidity in women with preterm prelabor rupture of membranes by performing a systematic review and meta-analysis. Materials and methods: We explored MEDLINE, Scopus, Embase, CINAHL, ClinicalTrials.gov and Cochrane Central Register of Controlled Trials for studies comparing the rate of a composite maternal infectious morbidity (either chorioamnionitis, endometritis or both) in women with preterm prelabor rupture of membranes that underwent a speculum only versus digital cervical examination at the time of diagnosis. Two reviewers separately ascertained studies, obtained data, and gauged study quality. The rate of a composite maternal infectious morbidity (either chorioamnionitis, endometritis or both) were compared and odds ratios (ORs) with 95% confidence intervals (CIs) were estimated. Results: Four cohort studies, reporting on 1213 women were identified. The median point prevalence of the composite maternal infectious morbidity was 26% (interquartile range 15–35%) in women who had a speculum examination only compared to 33% (interquartile range 22–42%) in women who underwent a digital examination. The overall maternal composite infectious morbidity rate in women that had a speculum examination only was less compared to women that had undergone a digital examination (pooled OR 0.75, 95% CI 0.58–0.98, I 2 17%). The weighted mean length of latency in women with preterm prelabor rupture of membranes was longer in individuals evaluated by speculum only versus digital examination, 6.6 d versus 2.9 d (mean difference 4.5 d, 95% CI 1.4 to 7.8, I 2 99%). Conclusion: Speculum examination only in women with preterm prelabor rupture of membranes is associated with less maternal infectious morbidity and longer latency periods.